EFEKTIVITAS PROGRAM DESA TANPA KEMISKINAN DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS (SDGs) DI DESA BANGBAYANG KECAMATAN SITURAJA KABUPATEN SUMEDANG - Rozaq, Abdul (JRPA - Journal of Regional Public Administration, 2024)
The purpose of this research is to determine the effectiveness of the Poverty-Free Village Program in Supporting the Sustainable Development Goals (SDGs) in Bangbayang Village, Situraja District, Sumedang Regency. The SDGs are an integrated effort to realize a poverty-free village. The method used in this study is a qualitative method with a descriptive type. The informants were determined using the purposive sampling technique, so that five research informants were obtained, namely: Village Government Administration, Development Implementation, Community Empowerment, Community Development and Disaster Management. Data collection techniques are literature studies and field studies consisting of observation, interviews, and documentation. Meanwhile, data processing is carried out using data reduction, data display, and data conclusion drawing/verification. Based on the results of the study, it was concluded that measuring program effectiveness was seen from the accuracy of program goals, program socialization, program objectives, program monitoring has been running effectively but not optimally, because it is hampered by limited budgets so that it hinders to achieve program goals effectively. The inhibiting factors lie in budget mapping, human resources, support provided is not holistic, lack of understanding of SOPs, so efforts are made to increase the capacity of implementers through training and coordination with related parties to ensure holistic policies. Suggestions in this study include strengthening mechanisms to verify program goals, developing UMKM businesses, and strengthening collaboration to support more effective and sustainable empowerment.